2021
DOI: 10.1111/imj.15045
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world outcomes for neoadjuvant capecitabine versus infusional 5‐fluorouracil in the treatment of locally advanced rectal cancer

Abstract: Background Neoadjuvant chemoradiation therapy is standard‐of‐care treatment for locally advanced rectal cancer (LARC). A pathological complete response (pCR) following chemoradiation therapy is an early indicator of treatment benefit and associated with excellent survival outcomes, with capecitabine largely replacing infusional 5‐fluorouracil as the choice in routine care of LARC. Aims To analyse the uptake of capecitabine usage over time, and on the back of clinical trial data demonstrating equivalence betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…We read with great interest the remarkable study by Loft et al, comparing capecitabine or 5-fluorouracil (FU)'s efficacy in the neoadjuvant chemoradiotherapy of rectal cancer in a real-life setting. 1 The authors observed significantly decreased complete pathological response (pCR) rates with the capecitabine, which was rather unexpected. As shown in the study, capecitabine largely replaced 5-FU in the chemoradiotherapy of rectal cancer with the convenience of oral use and comparable efficacy.…”
mentioning
confidence: 97%
See 3 more Smart Citations
“…We read with great interest the remarkable study by Loft et al, comparing capecitabine or 5-fluorouracil (FU)'s efficacy in the neoadjuvant chemoradiotherapy of rectal cancer in a real-life setting. 1 The authors observed significantly decreased complete pathological response (pCR) rates with the capecitabine, which was rather unexpected. As shown in the study, capecitabine largely replaced 5-FU in the chemoradiotherapy of rectal cancer with the convenience of oral use and comparable efficacy.…”
mentioning
confidence: 97%
“…As shown in the study, capecitabine largely replaced 5-FU in the chemoradiotherapy of rectal cancer with the convenience of oral use and comparable efficacy. 1,2 The authors pointed out the relative lack of data comparing 5-FU and capecitabine in the modern era, 1 with only one recent study from Australia identifying the inferior outcomes with capecitabine. 3 We agree with the authors' concerns and thank them for giving a perspective on this important issue.…”
mentioning
confidence: 99%
See 2 more Smart Citations